PEMODELAN PERUBAHAN PENGGUNAAN LAHAN DI KABUPATEN KAMPAR - Muhammad Fadhli; Rifardi Rifardi; Suardi Tarumun (Jurnal Ilmu Lingkungan, 2020)
This study aims to identify the types of land use and patterns of land use change in Kampar District. This study uses a survey method with visual interpretation techniques Landsat imagery in 1998,2008,2018 using geographic information systems (GIS). The results showed that 12 types of land use in Kampar district in 1998-2008-2018 were: 1) forest, 2) plantation forest, 3) plantation, 4) mixed plantation, 5) dry land agriculture, 6) rice field, 7 ) shrubs, 8) built up land, 9) mines, 10) open, 11) ponds, and 12) bodies of water. The patterns of land use change in Kampar Regency in the period 1998-2008-2018 were 187 patterns. There are 2 types of patterns of change, namely 1) the pattern of change from vegetated land use to vegetated land use and 2) the pattern of changes in the use of vegetated to non-vegetated land. The first type with the most dominant pattern based on the area of change include: 1) forests - plantations - plantations, 2) mixed plantations - plantations - plantations 3) Forests – plantation forests - plantation forests. The second type with a pattern of change based on area includes: 1) forest – forest - open, 2) mixed plantation - built up land – built up land, 3) mixed plantation - mixed plantation - mine.